Effect of chitosan oligosacharide on the inhibition and apoptosis of ovarian carcinoma SKOV-3 cells - Gao, Zong-Hua; Lv, Yao-Feng; Huo, Guan-Hua (Zhong yao cai, 2012)
To explore the effect and mechanism of inhibition and apoptosis of SKOV-3 cells induced by Chitosan oligosaccharide. Human ovarian cancer SKOV-3 cells were treated by various concentrations of Chitosan oligosaccharide. The inhibition of cell proliferation was tested by MTT. Apoptosis induced by Chitosan oligosaccharide was analysed by flow cytometry and agarose gel SKOV-3 cells DNA ladder electrophoresis. Chitosan oligosaccharide could efficiently inhibit SKOV-3 cells proliferation in a dose-dependent manner. Also, the significantly apoptosis of SKOV-3 cells induced by Chitosan oligosaccharide was confirmed through flew cytometry with Annexin V/PI double labels and agarose gel DNA ladder electrophoresis. Chitosan oligosaccharide can efficiently inhibit SKOV-3 cells proliferation and induce its obviously apoptosis.